2009
DOI: 10.1057/jphp.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of traumatic stressors in civilian occupational settings

Abstract: We use the literature reporting prevalence and aetiology of post-traumatic stress disorder (PTSD) in first responders as a catalyst to discuss for organisations the policy implications for prevention and intervention of psychiatric morbidity. We searched PubMed and Google to identify studies and reports of mental health and behavioural problems in occupations including police, fire, and emergency service workers. The prevalence of PTSD ranged from 6 per cent to 32 per cent. Biological markers of PTSD, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 41 publications
(37 reference statements)
2
57
0
Order By: Relevance
“…These results underscore the importance of mandatory screening programs for groups exposed to high levels of trauma and disaster, as concluded by other studies of disaster workers (McFarlane, Williamson, & Barton, 2009). Individuals with a trauma history, comorbid major depression, and greater occupational exposure are at risk for chronic PTSD that was still evident 6 years after the event.…”
Section: O N C L U S I O Nsupporting
confidence: 79%
“…These results underscore the importance of mandatory screening programs for groups exposed to high levels of trauma and disaster, as concluded by other studies of disaster workers (McFarlane, Williamson, & Barton, 2009). Individuals with a trauma history, comorbid major depression, and greater occupational exposure are at risk for chronic PTSD that was still evident 6 years after the event.…”
Section: O N C L U S I O Nsupporting
confidence: 79%
“…Furthermore, some studies have indicated that signs of inflammation may not necessarily correlate with the clinical symptoms of PTSD in a direct manner [15,16], and therefore the inclusion of one's immunological state along with the clinical symptom and severity of PTSD may provide further details of one's diagnostic state for PTSD in a more comprehensive manner. Moreover, considering that PTSD also has a late-onset tendency for clinical symptom development [17], incorporating data on the inflammatory state in the acute aftermath of trauma may help promote various strategies of early prevention and intervention for PTSD, as opposed to being solely dependent on the emergence of clinical symptoms as markers of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Except for studies by external occupational health experts examining the occupational health needs arising at workplaces during large-scale disasters, 25,26 few case reports on this matter have been published. 27,28 When the cause of the disaster is attributable to errors on the part of the company, they may be reluctant to disclose information on health issues during disasters.…”
mentioning
confidence: 99%